2015
DOI: 10.1177/1756287215589250
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of mirabegron compared with solifenacin in overactive bladder patients dissatisfied with previous antimuscarinic treatment due to lack of efficacy: results of a noninferiority, randomized, phase IIIb trial

Abstract: Objective: To compare the efficacy and safety of mirabegron 50 mg and solifenacin 5 mg in overactive bladder (OAB) patients dissatisfied with previous antimuscarinic treatment due to lack of efficacy. Patients and methods: This randomized, double-blind, phase IIIb, noninferiority study, enrolled male and female patients aged ⩾18 years old, with symptoms of OAB for ⩾3 months, who were dissatisfied with their previous antimuscarinic drug due to lack of efficacy. A total of 1887 patients were randomized to receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
84
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(88 citation statements)
references
References 21 publications
3
84
0
1
Order By: Relevance
“…To our knowledge, this is the first study to compare the efficacy and safety between mirabegron and imidafenacin. We found that the efficacy of mirabegron was comparable with that of imidafenacin, which is consistent with previous wherein solifenacin 18 or tolterodine 8 were used as antimuscarinic agents. However, the safety of mirabegron treatment was superior to that of imidafenacin treatment due to certain antimuscarinic effects.…”
Section: Discussionsupporting
confidence: 92%
“…To our knowledge, this is the first study to compare the efficacy and safety between mirabegron and imidafenacin. We found that the efficacy of mirabegron was comparable with that of imidafenacin, which is consistent with previous wherein solifenacin 18 or tolterodine 8 were used as antimuscarinic agents. However, the safety of mirabegron treatment was superior to that of imidafenacin treatment due to certain antimuscarinic effects.…”
Section: Discussionsupporting
confidence: 92%
“…The post hoc analysis of a randomized European‐Australian phase 3 trial showed that mirabegron had a numerically positive treatment effect on incontinence and micturition frequency in patients who discontinued prior antimuscarinics regardless of insufficient efficacy or poor tolerability as well as in those who were treatment‐naïve . Another phase 3 trial demonstrated that mirabegron was similarly efficacious to solifenacin in OAB patients dissatisfied with previous antimuscarinic treatment because of lack of efficacy . In real‐world situation, mirabegron achieved improvement of OAB symptoms in 60% of the patients who did not benefit from prior antimuscarinics and bladder drill .…”
Section: Discussionmentioning
confidence: 99%
“…One randomized double blind phase IIIb noninferiority study enrolled 1887 patients who had failed antimuscarinic therapy and randomized them to solifenacin 5 mg or mirabegron 50 mg for 12 weeks [Batista et al 2015]. The primary efficacy endpoint was change in baseline to end of study in mean number of micturitions per 24 hours.…”
Section: Efficacy and Safety Of Mirabegronmentioning
confidence: 99%